Pengaruh Ukuran Perusahaan, Pertumbuhan penjualan,dan leverage terhadap profitabilitas melalui rasio Roa pada sektor Food & Beverage dalam BEI periode 2015-2019 - Mia Natalia Nainggolan; Andre Sirait; Okky Nawa Nasution; Fuji Astuty (Politeknik Ganesha Medan, 2022)
The research we created with the aim of testing the influence of company size, sales growth, and leverage to the profitability ratio of Food & Beverage companies in the Indonesian stock exchange this research in carrying out their research using illustration as many 74 sampels listed on the Indonesian impact exchange. Based on the results of the analysis and efficiency of company size and sales growth partially has no effect on profitability but leverage is partially influential so the first and second hypothesis are rejected but the third hypothesis is accepted. Based on the results of the company size, sales growth and leverage is accepted Keywords: Company size, Sales growth, Leverage, Roa Profitability